A novel knee exoskeleton for overweight person - Saleem, Azizullah; Khan, Md. Raisuddin; Ahmmad, Syed Masrur (IEEE, 2015)
Overweight person experiences 2.9-4.7 times load of the bodyweight at the knee joint during walking. Research has shown that two main muscles which are vastus medial and gastrocnemius muscles contribute to the stressing of the knee joint during walking. In this research a light weight exoskeleton consisting of a frame and a compression spring with mechanisms for adjusting compression of the spring is developed. The research investigated the effectiveness of this exoskeleton compared to knee band by conducting experiment with compression spring deflection set to a suitable value. The result shows that the average percentage reduction of the gastrocnemius muscle activity is more than 50% for both the knee band and exoskeleton